Lexicographic Concepts Al-Munawwir Dictionary (Arab-Indonesian) Perspective Ali al-Qosimi - Syarifaturrahmatullah, Syarifaturrahmatullah; Sutaman, Sutaman; Aydın Yokmaç; Uril Bahruddin (Diwan Media Pustaka, 2024)
The al-Munawwir Dictionary by Ahmad Warson Munawwir is one of the most popular dictionaries for Arabic language learners in Indonesia. The use of dictionaries is undoubtedly beneficial for students in understanding the meaning of words and how they are used in oral and written expression. This study aims to describe the lexicography concept of the al-Munawwir dictionary and how the al-Munawwir dictionary is weighed through the perspective of al-Qosimi. This study uses a qualitative approach with a type of research in the form of library research. The primary source of this research is the al-Munawwir dictionary, while the secondary sources are books, journals, and other sources that follow the research theme. Data collection uses documentation techniques. The collected data were analyzed through three stages (Miles and Huberman): data condensation, data display, and data verification. The results of the study show that the al-Munawwir (Arabic-Indonesian) dictionary can be categorized as 1) a language dictionary (Al-Mu'jam al-Lughawi), 2) a bilingual dictionary (al-Mu'jam al-Tsunaiyatu al-Lughah), 3) extensive dictionary (al-Mu'jam al-Kabir), 4) general dictionary (al-Mu'jam al-Aam), and 5) word dictionary (Mu'jam al-Alfadzh). This dictionary fulfills 16 of the 25 components of the content conveyed by Al-Qosimi. This dictionary met 9 out of 10 criteria, especially in the central part. This shows that in terms of content, this dictionary is excellent because the central part is not equipped with a postulate of use.